2022
DOI: 10.3389/fimmu.2022.925762
|View full text |Cite
|
Sign up to set email alerts
|

Association of gestational diabetes mellitus and negative modulation of the specific humoral and cellular immune response against Toxoplasma gondii

Abstract: In order to evaluate and compare the specific immune response of pregnant women (PW) chronically infected with Toxoplasma gondii, with and without gestational diabetes mellitus (GDM), and the humoral response of their respective newborns (NB), the study was carried out on 81 PW (34 GDM and 47 controls) from whose medical records the results of the oral glucose tolerance test (OGTT) were obtained, and blood samples were collected at the third trimester of pregnancy; also, on 45 NBs (20 GDM and 25 controls) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Moreover, recently, our study group showed that pregnant women with gestational diabetes had lower anti- T. gondii than those without diabetes. They also had a higher number of T lymphocytes expressing activation and exhaustion markers (CD28 + and PD-1), a lower number of CD4 + T cells producing IFN-γ, IL-10, and IL-17, and lower secretion of IL-17, IL-4, TNF, and IL-2 after their PBMCs are challenged in vitro with T. gondii antigens, which indicates the importance of monitoring patients with immunosuppression, even if it is transient [ 37 ]. For this reason, we try to evaluate some parameters of cell expression and cytokine production in vitro after nonspecific stimulation and a stimulation with total soluble Toxoplasma gondii antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recently, our study group showed that pregnant women with gestational diabetes had lower anti- T. gondii than those without diabetes. They also had a higher number of T lymphocytes expressing activation and exhaustion markers (CD28 + and PD-1), a lower number of CD4 + T cells producing IFN-γ, IL-10, and IL-17, and lower secretion of IL-17, IL-4, TNF, and IL-2 after their PBMCs are challenged in vitro with T. gondii antigens, which indicates the importance of monitoring patients with immunosuppression, even if it is transient [ 37 ]. For this reason, we try to evaluate some parameters of cell expression and cytokine production in vitro after nonspecific stimulation and a stimulation with total soluble Toxoplasma gondii antigens.…”
Section: Discussionmentioning
confidence: 99%